MY JOURNEY TO BECOMING A POLYGLOT AND SYNCHRONIC INTERPRETER - Turg‘unboyeva Oynura To‘lqinboy qizi (Лучшие интеллектуальные исследования, 2024)
Annotation. This article, written by Oynura, a 9th-grade student from Chust, Namangan, explores her passion for learning multiple foreign languages and her dream of becoming a polyglot and synchronic interpreter. It discusses the reasons behind her aspirations, the steps she is taking to achieve her goals, and the challenges she anticipates.